The advantages of using photographs and video images in telephone consultations with a specialist in paediatric surgery - Ibrahim Akkoyun (Wolters Kluwer Medknow Publications, 2012)
Background: The purpose of this study was to evaluate the advantages of a telephone consultation with a specialist in paediatric surgery after taking photographs and video images by a general practitioner for the diagnosis of some diseases. Materials and Methods: This was a prospective study of the reliability of paediatric surgery online consultation among specialists and general practitioners. Results: Of 26 general practitioners included in the study, 12 were working in the city and 14 were working in districts outside the city. A total of 41 pictures and 3 videos of 38 patients were sent and evaluated together with the medical history and clinical findings. These patients were diagnosed with umbilical granuloma (n = 6), physiological/pathological phimosis (n = 6), balanitis (n = 6), hydrocele (n = 6), umbilical hernia (n = 4), smegma cyst (n = 2), reductable inguinal hernia (n = 1), incarcerated inguinal hernia (n = 1), paraphimosis (n = 1), burried penis (n = 1), hypospadias (n = 1), epigastric hernia (n = 1), vulva synechia (n = 1), and rectal prolapse (n = 1). Twelve patients were asked to be referred urgently, but it was suggested that only two of these patients, who had paraphimosis and incarcerated inguinal hernia be referred in emergency conditions. It was decided that there was no need for the other ten patients to be referred to a specialist at night or at the weekend. All diagnoses were confirmed to be true, when all patients underwent examination in the pediatric surgery clinic in elective conditions. Conclusion: Evaluation of photographs and video images of a lesion together with medical history and clinical findings via a telephone consultation between a paediatric surgery specialist and a general practitioner provides a definitive diagnosis and prevents patients from being referred unnecessarily.